From converting the pagan to dialogue with our partners : HMI's fifty years work of evangelism and interfaith relations - Souza, Andreas D'; D'Souza, Andreas; Henry Martyn Institute of Islamic Studies; I.S.P.C.K. (Organization) (New Delhi : Indian Society for Promoting Christian Knowledge, 2009)
Contributed research articles previously published in Bulletin of the Henry Martyn Institute of Islamic Studies.
Keywords: Henry Martyn Institute of Islamic Studies -- History; Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Missions to Muslims -- India; Evangelicalism -- Relations -- Islam